2011
DOI: 10.1128/aac.01733-09
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Resistance Profile Determination of Two Second-Generation HIV-1 Integrase Inhibitors Using a Panel of Recombinant Viruses Derived from Raltegravir-Treated Clinical Isolates

Abstract: The integrase inhibitor raltegravir (RAL) is currently used for the treatment of both treatment-naïve and treatment-experienced HIV-1-infected patients. Elvitegravir (EVG) is in late phases of clinical development. Since significant cross-resistance between RAL and EVG is observed, there is a need for second-generation integrase inhibitors (INIs) with a higher genetic barrier and limited cross-resistance to RAL/EVG. A panel of HIV-1 integrase recombinants, derived from plasma samples from raltegravir-treated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…Only N155 and Q148 are reported to confer crossresistance to EVG (19,(45)(46)(47), while Y143 is reported to be specific for RAL (48). Primary substitutions at positions G118 and R263 and a secondary substitution at position H51 in integrase were previously shown in cell culture selections to confer resistance to INSTIs, including RAL, MK-2048, and DTG (21)(22)(23)49).…”
Section: Discussionmentioning
confidence: 99%
“…Only N155 and Q148 are reported to confer crossresistance to EVG (19,(45)(46)(47), while Y143 is reported to be specific for RAL (48). Primary substitutions at positions G118 and R263 and a secondary substitution at position H51 in integrase were previously shown in cell culture selections to confer resistance to INSTIs, including RAL, MK-2048, and DTG (21)(22)(23)49).…”
Section: Discussionmentioning
confidence: 99%
“…E92Q is a nonpolymorphic mutation that has been selected in patients receiving either EVG (40)(41)(42)(43)(44) or RAL (39,40,45) and is associated with virological failure on EVG-based regimens (45). The A54A/V, A265A/V, and V277V/M partial substitutions were selected under INSTI pressure, but only the A265 position is conserved among HIV integrases of different subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Secondgeneration INSTIs have been developed, which possess a more robust resistance profile than RAL and EVG (3,21,27,33,67). These include MK-2048 (3, 4, 20, 67) and dolutegravir (DTG) (3,20,33,45,46,61,67).Selection studies have shown that MK-2048 can select a G118R resistance mutation (3), and during similar studies with DTG, changes were observed at positions E92, L101, T124, S153, and G193 (33,57,59). However, fold changes (FC) in susceptibility were moderate (FC, Ͻ2.5) for all of these substitutions; the substitutions at the well-characterized polymorphic positions L101 and T124 did not increase DTG or RAL FC (33, 68).…”
mentioning
confidence: 99%
“…Three main resistance pathways have been identified for RAL, involving initial mutations of the N155, Q148, and Y143 residues within IN (11). Both N155 and Q148 confer cross-resistance to EVG (19,41,47,67), while Y143 has been reported to be specific for RAL (44). Numerous secondary mutations confer low levels of resistance against both drugs (reviewed in reference 47).…”
mentioning
confidence: 99%
See 1 more Smart Citation